(untitled) (Eurasian Research Bulletin, 2025)
This article talks about the problem of professional pedagogical training of future pedagogical personnel, especially students of pedagogical education, and its scientific and pedagogical analysis. Also, information on the problem of professional pedagogical training of future pedagogical personnel and its scientific-pedagogical analysis is provided